Analysis of Scientific Views to the Structure of Informative Competence of Students of Universities - Dolyns’kyi, Yevhen (Pedagogical Discourse, 2012)
The article deals with modern scientific pedagogical views at formation of structure of informative competence of students of universities, and also own vision of structure of informative competence is formed.